Analysis of Recent Erosion Hazard Levels and Conservation Policy Recommendations for Lesti Subwatershed, Upper Brantas Watershed - Andi Setyo Pambudi; Setyo Sarwanto Moersidik; Mahawan Karuniasa (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
The reduced age function of Sengguruh Dam/Reservoir due to erosion in the upper of Brantas Watershed (Lesti Subwatershed area) interferes with its role in flood control, irrigation water supply and the supply of most of the hydroelectricity in East Java Province, Indonesia. This study aims to estimate erosion, analyze the interrelationship of the causative factors and provides environmental conservation direction. The research method uses mixed methods. The quantitative method of erosion rates is done by calculating the Modify Universal Soil Loss Equation which is supported by GIS tools. The qualitative method is carried out with questionnaires and interviews in the Lesti Subwatershed area. The results showed that the current erosion rate in each ha of land (average) in the Lesti Subwatershed was 153,868 tons / ha / year (exceeding the tolerable erosion rate of 30 tons / ha / year). The rate of erosion in the Lesti Subwatershed has always increased in the last 14 years. Of the 12 Subdistricts in the Lesti watershed, as many as 6 Subdistricts are identified as having high levels of Erosion Hazards so that they were a priority to be handled, namely in the Wajak, Dampit, Tirtoyudo, , Gedangan, Sumbermanjing Wetan and Bantur Subdistricts. Dampit Subdistrict, Turen Subdistrict and Gondanglegi Subdistrict also face behavioral problems and high population pressure compared to other Subdistricts. Research also shows that there is a relationship between erosion and knowledge, attitudes and behavior of the community in the form of population pressure and land use patterns. It is recommended that environmental conservation directives focus on these 6 Subdistricts through the application of soil and water conservation. The results of spatial analysis at priority locations suggest conservation measures in the form of law enforcement or counseling, and community empowerment to increase the ability and independence of the community through providing access to resources, education, and training.